Strengthening Environmentally Friendly Behavior Through Waste Sorting and Recycling Programs Increasing Value Added Healthy Islamic Boarding Schools and Zero Waste - Nihayatu Aslamatis Solekah; Jumriyah Jumriyah (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2023)
Applying the zero-waste concept is needed so that waste management in urban areas is not only more environmentally friendly. It's no longer just a trend, but this zero-waste has developed into a norm among the millennial generation in Indonesia. This service aims to strengthen environmentally friendly behaviour through sorting organic and inorganic waste and training in recycling inorganic waste into valuable products. The method used Participatory Action Research (PAR). This service found that students at PPAI An-Nahdliyah responded positively to environmentally friendly behaviour by sorting waste and received high creativity in recycling plastic bottle waste into valuable products, such as flower bouquets, pencil cases, etc. However, the sustainability of this program still needs to be improved. Therefore, this service recommends continuously improving students' resources to behave environmentally friendly and utilize their waste through reduction, reuse or recycling so that a zero-waste lifestyle is formed and supervision between each PPAI An-Nahdliyah student.